A Feasibility Study on Using the Facilities of Health Centers for Developing a Laboratory Network on Vectors and Reservoir Hosts of Cutaneous Leishmaniasis in Iran - Mohammad Reza Yaghoobi-Ershadi; Amir Ahmad Akhavan; Mohammad Reza Shirzadi; Seyedeh Zohreh Hosseini; Oscar Daniel Salomon; Ahmad Ali Hanafi-Bojd; Yavar Rassi (Tehran University of Medical Sciences, 2022)
Background: Cutaneous leishmaniasis is an ancient endemic disease in Iran and continues to be a growing health threat to community development and the environment. This paper explains how to use the facilities of health centers for developing a laboratory network on vectors and reservoir hosts of cutaneous leishmaniasis in Iran. Methods: A literature search was performed of the relevant multiple databases to include studies on vectors and reservoirs of cutaneous leishmaniasis in Iran. A team of experienced experts was performed. After holding several meetings, field visits and organizing workshops, the activities of laboratories were determined at three levels. Results: Entomological studies showed that 5 species of the genus Phlebotomus and 10 species of the genus Sergentomyia are active in the south, 4 species of the genus Phlebotomus and one species of the genus Sergentomyia in the central part and 5 species of the genus Phlebotomus and 2 species of the genus Sergentomyia in the north east. Reservoir hosts were identified in the study areas. The tasks of laboratories were regulated at different levels. Conclusion: The Iranian Ministry of Health and Medical Education should prioritize the employment of capable persons in the field of Medical Entomology and Vector Control. The survival of this laboratory network depends on hiring and employing interested and persistent people. The universities of Medical Sciences that have the facilities to set up this network will be a very effective partner in the control of the disease in high risk areas. The results can be used in neighboring countries.